Digital interventions for adolescents with type 1 diabetes to promote health literacy? A qualitative study on physicians’ perspective in Germany - Hürrem Tezcan-Güntekin; Aurélia Naoko Naef; Nadine Fischbock; Volker Eric Amelung (BMJ Public Health)
Introduction Adolescents with type 1 diabetes mellitus (T1D) require a high level of health literacy (HL) to prevent complications. It remains unclear what potential digital interventions have for promoting HL among adolescents with T1D, as viewed by physicians working with this target group. Additionally, it is unclear how the institutions (inpatient care and outpatient care) can support and facilitate the use of digital interventions to promote HL.Research design and methods An exploratory study was conducted using semistructured interviews with physicians (n=12) in Germany. The interview questions are based on a previous systematic review. The coding was conducted deductively and inductively using MAXQDA software. Subsequently, the interviews were analysed systematically through an iterative process of content analyses in line with Kuckartz et al.Results It was reported by the physicians that digital interventions are underused due to technical resources, lack of structural conditions, information and legal constraints. The utilisation of digital interventions to promote HL was heterogeneous and depended primarily on the willingness of the physicians. Communication strategy techniques were widely employed to motivate patients, an activity occurring mainly in-person, thus limiting the opportunity for the deployment of digital interventions.Conclusions To increase the use of digital interventions and improve HL, support for digital literacy skills could be implemented. Capacity building through patient-centred, interdisciplinary and participatory culture should be considered. The findings of this study can provide valuable insights for practice, research and policy.